PENGARUH KECERDASAN SPIRITUAL TERHADAP KOMITMEN ORGANISASI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PT Calmic Indonesia Cabang Palembang) - L. Suhairi Hazisma (Politeknik Negeri Sriwijaya, 2013)
The aim of this study is to investigate the effect of spiritual intelligence on organizational commitment with job satisfaction as intervening variable. The present study was conducted in PT Calmic Indonesia Cabang Palembang. There were 38 employees at PT Calmic Indonesia Cabang Palembang. Determination of the sample using a non-probability sampling approach, with a sampling technique using saturation sampling. This study uses two variables, namely the independent variable and the dependent variable. The independent variable in this study are: spiritual intelligence and job satisfaction while the dependent variable is organization commitment. Questionnaires measured using a Likert Scale. Test validity, reliability, coefficient of determination, and path analysis using SPSS. The findings indicate that spiritual intelligence has a positive influence on job satisfaction; job satisfaction has a positive influence on organizational commitment. Spiritual intelligence and job satisfaction has a positive influence on organizational commitment. As a result, the effect of spiritual intelligence on organizational commitment is mediated by job satisfaction.